2004
DOI: 10.1021/ac0493727
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Cell Separation Using Antibody Binding with Protein A Expressed on Bacterial Magnetic Particles

Abstract: Bacterial magnetic particles (BacMPs) are efficient platforms of proteins for surface display systems. In this study, mononuclear cells from peripheral blood were separated using BacMPs expressing protein A on the BacMP membrane surface (protein A-BacMPs), which were complexed with the Fc fragment of anti-mouse IgG antibody. The procedure of positive selection involves incubation of mononuclear cells and mouse monoclonal antibodies against different cell surface antigens (CD8, CD14, CD19, CD20) prior to treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(89 citation statements)
references
References 36 publications
0
89
0
Order By: Relevance
“…The procedure for positive selection involves incubation of mononuclear cells and mouse monoclonal antibodies against different cell surface antigens (CD8, CD14, CD19 and CD20) prior to treatment with protein A-BacMP complexes with rabbit anti-mouse IgG secondary antibodies. The average purities of the separated mononuclear cells of CD19 C and CD20 C were 97.5 and 97.6%, respectively (Kuhara et al 2004). Furthermore, more than 95% of the recovery ratio was obtained for these cells.…”
Section: Cell Separationmentioning
confidence: 88%
See 1 more Smart Citation
“…The procedure for positive selection involves incubation of mononuclear cells and mouse monoclonal antibodies against different cell surface antigens (CD8, CD14, CD19 and CD20) prior to treatment with protein A-BacMP complexes with rabbit anti-mouse IgG secondary antibodies. The average purities of the separated mononuclear cells of CD19 C and CD20 C were 97.5 and 97.6%, respectively (Kuhara et al 2004). Furthermore, more than 95% of the recovery ratio was obtained for these cells.…”
Section: Cell Separationmentioning
confidence: 88%
“…Because BacMPs consist of ferromagnetic iron oxide, they are easily separated from cell suspensions using a permanent magnet with no special column. We have therefore applied BacMPs to develop highly efficient magnetic cell separation (Kuhara et al 2004). BacMPs expressing protein A (protein A-BacMPs) bound to the Fc fragment of anti-mouse IgG antibodies were used to separate mononuclear cells from peripheral blood.…”
Section: Cell Separationmentioning
confidence: 99%
“…To enrich for target cells, cell surface antigens, such as cluster of differentiation (CD) antigens, were used as markers. CD8, CD14, CD19, CD20, and CD34 positive cells were efficiently enriched from peripheral blood (Kuhara et al, 2004;Matsunaga et al, 2006). The separated CD34 positive cells retained the capability of forming colonies as hematopoietic stem cells.…”
Section: Applications Of Antibody-magnetic Particlesmentioning
confidence: 97%
“…The major advantage of magnetic particles is that they can be easily manipulated by magnetic force, which enables rapid and easy separation of target molecules bound to the particles from reaction mixtures (Mirzabekov et al, 2000;Gu et al, 2003;Kuhara et al, 2004;Xu et al, 2004). Use of magnetic particles is beneficial for complete automation of steps, resulting in minimal manual labor and providing more precise results (Sawakami-Kobayashi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Protein release is effected by a change in pH or by eluting the column with a solution with a high concentration of imidazole. [12][13][14] Nanomaterials such as nanoparticles, nanotubes, and nanorods have been extensively used as complementary candidates for the effective separation of biomaterials [25][26][27][28][29][30] as well as in the field of biomedical diagnostics and therapeutics. [31][32][33][34][35][36][37] Previously we reported that twocomponent triblock magnetic nanorods with Au end blocks and a Ni interior block can be used as affinity templates for simple and efficient separation of His-tagged proteins from other proteins without affinity tags.…”
Section: Introductionmentioning
confidence: 99%